1983
DOI: 10.2172/5277693
|View full text |Cite
|
Sign up to set email alerts
|

Review of Hydrogen Isotope Permeability Through Materials

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 9 publications
10
106
1
6
Order By: Relevance
“…5) indicate the sequence of the measurements. The decrease in flux with decreasing temperature is similar to our results for Nb foil but is not predicted on the basis of solubility and diffusivity [10], suggesting that the sample was influenced by extrinsic factors, such as oxidation or interdiffusion between the Ta foil and its Pd coating. Although the Ta foil's temperature dependence resembles that of Nb foil, initial results suggest that Ta foil is less susceptible to hydrogen embrittlement.…”
supporting
confidence: 84%
“…5) indicate the sequence of the measurements. The decrease in flux with decreasing temperature is similar to our results for Nb foil but is not predicted on the basis of solubility and diffusivity [10], suggesting that the sample was influenced by extrinsic factors, such as oxidation or interdiffusion between the Ta foil and its Pd coating. Although the Ta foil's temperature dependence resembles that of Nb foil, initial results suggest that Ta foil is less susceptible to hydrogen embrittlement.…”
supporting
confidence: 84%
“…In most cases the gas flux of the membranes was reduced after sputtering as can be expected due to the relatively nonpermeable nature of the metal. Hydrogen permeation through Pt is negligible when compared to the gas transport through PEI at temperatures below 80 °C [28].…”
Section: Membrane Preparation and Testingmentioning
confidence: 99%
“…Pd is among the most active catalysts for H2 dissociation, the essential first step in hydrogen transfer across an alloy membrane, meaning that a single layer of Pd or a Pd-based alloy can act as a H-selective membrane. Although Steward's review [11] shows that many metals exhibit significantly greater permeability than Pd, their unfavorable surface properties mean they can only function as a membrane with addition of a thin Pd catalytic over-layer.…”
Section: Catalytic Dissociation Of Hydrogen Molecules By Pd and Nmentioning
confidence: 99%
“…This is driving the development of less-expensive alternative membrane materials. Steward's review of hydrogen permeability [11] showed several metals have equivalent or greater permeability than Pd. Furthermore, many of these metals, such as Ni, Co, Nb, Zr, cost in the range of USD 1-3 oz -1 , making them of great interest as potential Pd-alternatives.…”
Section: Introductionmentioning
confidence: 99%